The Role of Green Entrepreneurship in Achievement of Sustainable Development Goals Authors - Salar Basiri (Journal of Biotropical Research and Nature Technology, 2025)
Green entrepreneurship new and growing companies that create environmental value alongside economic and social value is moving from the margin of policy and research to the mainstream of strategies to sustainable development. This review synthesizes recent theoretical and empirical contributions to the role of green entrepreneurship (GE) in the contribution to the 2030 Agenda's Sustainable Development Goals (SDGs), with focus on mechanisms, effects, and enabling conditions. We discuss definitional accuracy with respect to sustainable and environmental entrepreneurship; map GE pathways to specific SDGs; amalgamate evidence on effects (including mixed findings); examine the functions of ecosystems, funds, regulation, human assets, and culture; and suggest measurement techniques and testing requirements. While robust evidence links GE with progress in SDGs that include clean energy (SDG 7), responsible consumption and production (SDG 12), industry and innovation (SDG 9), decent work and growth (SDG 8), and climate action (SDG 13), environmental impacts depend on context and policy design in terms of direction and strength. The review is succeeded by a pragmatic scorecard and agenda for researchers and policymakers to accelerate GE's role in the SDGs.